KAJIAN HUKUM ISLAM DAN HUKUM POSITIF TERHADAP PERKAWINAN BEDA AGAMA BERDASARKAN PUTUSAN MAHKAMAH AGUNG NOMOR 1400 K/PDT/1986 - Frida Ramadhani; Diding Rahmat (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
The phenomenon of interfaith marriages often occurs not only in various countries, but also in Indonesia, where this is widely practiced. This research aims to look at the phenomenon of interfaith marriage in qualitative form so that the final goal can be developed with specific concepts to provide specific conclusions with various updates. The research results show that interfaith marriages often occur in Indonesian society. In the Marriage Law No. 1 of 1974 concerning marriage there is a clear prohibition and in the Compilation of Islamic Law in Article 40 paragraph (c) and Article 44 the same is true. The same thing can also be seen in the MUI Fatwa. However, there are some opinions of ulama who allow interfaith marriages between Muslim men and women from people of the book.